Pemberian Insentif dan Motivasi serta Pengaruhnya terhadap Produktivitas Kerja dalam Perspektif Psikologi Islam - Peni Indrawati (Sekolah Tinggi Ilmu Ekonomi Syariah Riyadlul Jannah Mojokerto, 2021)
The purpose of this study was to examine and analyze the simultaneous, partial and dominant effect of the variable incentives and motivation on employee productivity. This research is explanatory (explaining) is